This distracted globe attending to distraction in Shakespeare's theatre - Edwards, Jennifer J. (Cambridge University Press, 2023)
This Element attends to attention drawn away. That the Globe is a 'distracted' space is a sentiment common to both Hamlet's original audience and attendees at the reconstructed theatre on London's Bankside. But what role does distraction play in this modern performance space? What do attitudes to 'distraction' reveal about how this theatre space asks and invites us to pay attention? Drawing on scholarly research, artist experience, and audience behaviour, This Distracted Globe considers the disruptive, affective, phenomenological, and generative potential of distraction in contemporary performance at the Globe
Title from publisher's bibliographic system (viewed on 04 May 2023)
Keywords: Shakespeare, William / 1564-1616 / Dramatic production; Shakespeare, William / 1564-1616 / Stage history; Globe Theatre (London, England : 1996- ); Distraction (Psychology) in literature; Distraction (Psychology)